The Greenspan effect words that move the world's markets - Sicilia, David B.; Cruikshank, Jeffrey L. (McGraw-Hill, 2000)
"By focusing on Alan Greenspan's public pronouncements as Fed chairman, The Greenspan Effect provides a concise, accurate distillation of Greenspan's thinking on today's most important economic topics. It presents an historic, solidly researched overview of how these pronouncements have affected Wall Street and other world financial markets.